Assessment of ChatGPT in the Prehospital Management of Ophthalmological Emergencies – An Analysis of 10 Fictional Case Vignettes - Knebel, Dominik; Priglinger, Siegfried; Scherer, Nicolas; Klaas, Julian; Siedlecki, Jakob; Schworm, Benedikt (Klinische Monatsblätter für Augenheilkunde, 2023)
Background The artificial intelligence (AI)-based platform ChatGPT (Chat Generative Pre-Trained Transformer, OpenAI LP, San Francisco, CA, USA) has gained impressive popularity in recent months. Its performance on case vignettes of general medical (non-ophthalmological) emergencies has been assessed – with very encouraging results. The purpose of this study was to assess the performance of ChatGPT on ophthalmological emergency case vignettes in terms of the main outcome measures triage accuracy, appropriateness of recommended prehospital measures, and overall potential to inflict harm to the user/patient.Methods We wrote ten short, fictional case vignettes describing different acute ophthalmological symptoms. Each vignette was entered into ChatGPT five times with the same wording and following a standardized interaction pathway. The answers were analyzed following a systematic approach.Results We observed a triage accuracy of 93.6%. Most answers contained only appropriate recommendations for prehospital measures. However, an overall potential to inflict harm to users/patients was present in 32% of answers.Conclusion ChatGPT should presently not be used as a stand-alone primary source of information about acute ophthalmological symptoms. As AI continues to evolve, its safety and efficacy in the prehospital management of ophthalmological emergencies has to be reassessed regularly.
Keywords: ChatGPT; artificial intelligence; AI; language model; emergencies; triage